Karakterisasi Pertanian Berkelanjutan di Pulau Kecil - Zasti Indrianty Joisangadji; Rima Melati; Suratman Sudjud; Abdul Rahmat Mandea (Jurnal Ilmu Pertanian Indonesia, 2024)
The character of Hiri Island, which is located in the cluster of small islands in North Maluku in the study of sustainable crop cultivation practices, has yet to be documented in the Islands Agriculture database. This research reveals local farmers' cultivation practices using production inputs. The methods used are observation and interviews. Respondents were determined by deliberate methods. Research variables included sustainable agriculture indicators such as land conservation, agroforestry, integrated pest control, protective crops, crop nutrient management, and crop diversification. Data were obtained through a closed questionnaire with "Yes" or "No" questions. The answer "Yes" was given a score of 1, while the answer "No" was a score of 0. Next, the data is tabulated and analyzed using descriptive analysis. The results showed that farmers on Hiri Island maintain agricultural productivity by implementing sustainable agricultural practices with several indicators such as water source management 42%, integrated pest control 50%, crop diversification 65%, crop nutrition management 65%, land conservation 75%, and agroforestry 83%. Farmers on this island have implemented the concept of sustainable agriculture, but it needs to be done continuously by maximizing cultivation practices on small islands. Keywords: hiri, small island characteristics, archipelago agriculture